Zaposlovanje oseb z začasno zaščito iz Ukrajine v sistemu agencijskega dela v Sloveniji - Krapež, Katarina (Podjetje in delo, 2022)
In February 2022, for the first time in history, the European Commission proposed the activation of the Temporary Protection Directive, which should provide displaced persons from Ukraine with a quick and easy way to obtain a temporary residence permit and access to education or the labour market in Member States. After the adoption of implementing regulations in Slovenia and obtaining a decision on their status, displaced persons from Ukraine have a recognised right to work, on the basis of which they could be employed, self-employed or work on the basis of civil contracts. Although persons with such protection can conclude a regular employment contract, in Slovenia this group of workers is typically employed in the system of temporary agency work. The article focuses on the characteristics of the agency work of asylum seekers and persons with (temporary) protection in Slovenia, highlighting the specifics of the employment processes of displaced persons from Ukraine. A review of secondary sources and data obtained in interviews with representatives of temporary employment agencies shows that state institutions were not adequately prepared to activate such a mechanism. This has led to delays in issuing the decisions (it was planned to issue ID cards) that displaced persons from Ukraine need to get involved in work. The response of the labour market in Slovenia was notably inclusive, temporary work agencies and other employers showed a high willingness to accept candidates from Ukraine into the work process, among which qualified and educated staff were predominant. Delays in obtaining their status, difficult access to candidates, the gap between supply and demand on the Slovenian labour market, poor language skills, and the lack of documentation were key challenges faced by stakeholders in recruitment processes.
Keywords: agencijsko delo; displaced persons from Ukraine; employment; employment agencies; kadrovske agencije; osebe z začasno zaščito; persons under temporary (international) protection; razseljevanje iz Ukrajine; Slovenia; Slovenija; temporary agency work; zaposlovanje